2019
DOI: 10.4314/ijs.v21i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Potential occupational health effects of municipal solid waste management in Nigeria, the case of Lagos and Ibadan

Abstract: Municipal Solid Waste Management (MSWM), which include generation of wastes, collection, transportation, recycling and reuse, and disposal poses threat to humans especially the waste handlers and managers and the entire ecosystem. In this study, relevant data and information about the health hazards associated with MSWM were gathered using structured questionnaires administered to three different categories of municipal solid waste (MSW) handlers namely; Domestic Waste Handlers (DWHs), Highway Waste Managers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…Only a small fraction of the waste workers go for routine medical checks. The findings are in line with studies by Adeyi & Adeyemi (2019), where it was observed that lack of medical insurance scheme for the different categories of solid waste managers is responsible for many of them not having routine medical check-ups to take care of their health. The majority of the solid waste workers have no formal education, this may adversely affect their understanding about Covid 19, disease and the importance of vaccines, and this concurs with findings by Adekiya (2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Only a small fraction of the waste workers go for routine medical checks. The findings are in line with studies by Adeyi & Adeyemi (2019), where it was observed that lack of medical insurance scheme for the different categories of solid waste managers is responsible for many of them not having routine medical check-ups to take care of their health. The majority of the solid waste workers have no formal education, this may adversely affect their understanding about Covid 19, disease and the importance of vaccines, and this concurs with findings by Adekiya (2021).…”
Section: Discussionsupporting
confidence: 91%
“…These include fatigue, back pain, chest pain cough, diarrheal, eye infection, difficulty in breathing and skin rash. These findings corroborated studies by Gizaw et al (2014), Baral (2018), Mol et al (2019) and Adeyi & Adeyemi (2019). Only a small fraction of the waste workers go for routine medical checks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, the authors recommended as a vital response to raise the workers awareness, besides enlightenment training, to survive the health hazards and its risks. [31,32] A periodic, objective and documented assessment and auditing of the dumpsites and their workers is a necessary concern to minimize the health issues that these workers face. Vaccination against HBV is an effective measure to control such an infection.…”
Section: Discussionmentioning
confidence: 99%
“…The waste scavengers mainly search through piles of unwanted goods to recover easily recyclable materials such as glass, metal and plastic, which they sell to scrap dealers, who then process the waste and sell it on either to be recycled or to be used directly by the industry. Most studies report that waste scavengers constitute disadvantaged and vulnerable segments of the population [2].…”
Section: Introductionmentioning
confidence: 99%